Static structure factor of macroparticles in dusty plasmas (International Journal of Mathematics and Physics, 2013)
Equilibrium distribution functions are studied based on the previously proposed pseudopotential model of dust particles interaction in the plasma, which takes into account both the finite-size and the screening effects. Consideration is made in the framework of the renormalization theory of plasma particles interaction leading to the so-called generalized Poisson-Boltzmann equation. The main idea is to re-use the renormalization theory to treat the dust component of the plasma. Initially, a generalized Poisson-Boltzmann equation is used to determine characteristics of the interaction between two isolated dust particles. The interaction potential obtained in that way does not contain the number density of dust particles and can be utilized for further theoretical considerations. In particular, this paper re-uses the Poisson-Boltzmann equation to derive equilibrium distribution functions of dust particles. Such an approach allows one to obtain analytical expressions for the static structure factor of the dust particles. Non monotonic behavior of the static structure factor of the dust particles is observed at different values of plasma parameters, which may indicate the short-range or even long-range order formation in the system.